DEVELOPING A COMMUNITY-BASED ISLAMIC EDUCATION CURRICULUM A MULTICULTURAL APPROACH IN LEARNING TO IMPROVE INTER-CULTURAL TOLERANCE (A Study at Nurul Ihsan Islamic Boarding School in Bontang City, East Kalimantan) - Zulkifli, Zulkifli; Zamroni, Zamroni; Tamam, Badrut (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This study is a qualitative research aimed at analyzing the implementation of multicultural values in pesantren education. Data were collected through observation, interviews, and documentation at Pesantren Nurul Ihsan Bontang. The pesantren integrates Islamic teachings with principles of tolerance and diversity in its curriculum. The subjects of this study were the santri (students) and the pesantren caregivers. The findings indicate that the implementation of multicultural values in religious education enhances the santri's understanding of the importance of interfaith and cultural tolerance. Activities such as interfaith group discussions and weekly social programs support the creation of an inclusive environment. Furthermore, interviews with the pesantren caregivers revealed that this approach also strengthens the sense of togetherness and mutual respect among the santri